KEPEMIMPINAN PENDIDIKAN DI ERA DIGITAL: PERSPEKTIF MANAJEMEN PENDIDIKAN - Hardi, SUHARDI; Noviadi Nugroho, Mochammad (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2025)
AbstrackThis study examines the complexities of educational leadership in the digital era through a comprehensive analysis of six fundamental leadership characteristics, six systematic educational management strategies, and five implementation challenges in Indonesian educational institutions. Through a systematic literature review methodology, the research reveals that successful digital transformation requires leaders to possess integrated competencies encompassing digital vision, comprehensive digital literacy, spiritual foundation, adaptive-innovative capabilities, collaborative skills, and change management expertise. The findings demonstrate that effective implementation depends on systematic management strategies, including comprehensive strategic planning, human resource development, integrated information systems, digital learning optimization, network infrastructure strengthening, and strategic partnership development. Despite facing significant challenges such as digital gaps, human resource readiness, financial constraints, data security, and character value integration, the study shows that multi-stakeholder collaboration-based solutions have proven effective in supporting sustainable digital transformation while maintaining fundamental educational values. The research contributes to theoretical understanding by highlighting the integration of technological, pedagogical, and managerial competencies in digital educational leadership, while providing practical implications for developing contextual digital transformation roadmaps, strengthening digital competencies, and building ethical digital culture through strategic partnerships.Keywords: educational leadership, digital era, educational management, digital literacy, digital transformation